O lugar de Germano Gultzgoff: um olhar sobre a produção do arquiteto - Ana Lúcia Bertini Mardegan (2014)
This research presents the architectural production, relatively unknowned, by the architect Germano Gultzgoff at Uberaba, Minas Gerais. Although formed in a school at the São Paulo state, the architect migrates to Uberaba, Triângulo Mineiro and produces its architecture, inthis locality, among the 1950 to 1990. Besides to get the original projects in municipal agencies, we elaborated a catalog card of each building that contains not only the architectural project as well as updated data of identified buildings as, for example, location, uses, areas and images. The identification of each building followed a decade criteria rating.After the identification of the buildings, they were georeferenced and then preliminary analysed.